Modelling torus behaviour in a fish farming cage - Haruka Nishikawa; Hisashi Fukushima (Aquaculture, Fish and Fisheries, 2022)
Abstract Since it is not usually possible to observe all of the fish in a school, it is difficult to monitor farmed fish in a crowded cage with the aim of scrutinising their condition. One possible solution to this problem is the use of simulations. The aim of this study is to simulate fish movement in a cage to be able to propose an optimal monitoring method based on limited observations made by instruments. In this study, we observed a Yellowtail (Seriola quinqueradiata) school in a fish cage at a fish farm and attempted to simulate their movement. The Yellowtail, while milling in a cage, forms a stable truncated cone‐shaped school. We successfully reproduced this shape of school by including the effects of negative phototropism and the hypothetical forces that fish experience from the cage wall, in addition to the forces of attraction, repulsion and orientation that have been postulated in previous studies. We also included the effect of intraspecific interaction. We hypothesise that longer fish exert a greater repulsive force on smaller fish. The results of our simulation suggest that the position of any fish in a school is thus a function of its length.